Development of Setaparula Monopoly Media on the Theme of The Beauty of Diversity in My Country in Social Science Learning - Zerri Rahman Hakim (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
This study aims to determine feasibility of setaparula monopoly media development (weapons, dance, clothes, home, songs) on the beautiful themes of diversity in my country in learning ips of fourth grade primary school which developed and get value from experts, and to find out students' responses to setaparula monopoly media development (weapons, dance, clothes, home, songs) on the beautiful themes of diversity in my country in learning ips of fourth grade primary school. This research was conducted at SD Negeri Panunggangan 1 with research subjects in fourth grade with 10 students in a limited trial. The type of research used in the development research method (Research and Development) of Borg and Gall which is modified by Sugiyono consists of 6 stages, namely: the problem analysis stage, the data collection stage, the product design development stage, the product design validation stage, the product design revision (revision) stage, and the product trial stage. The instrument used was a questionnaire sheet for expert validation and student responses. The results of the validation test by experts (media experts, material experts, linguists, and education experts) on the quality of the monopoly media setaparula (regional weapons, traditional dances, traditional clothes, traditional houses, regional songs) which developed are included in the appropriate criteria with a percentage of the assessment amounted to 78.21%. The results of the limited trial of students to the monopoly media setaparula (regional weapons, traditional dances, traditional clothes, traditional houses, folk songs) getting very feasible criteria with an assessment percentage of 100%. Based on the results of the study, it can be concluded that the monopoly media setaparula (regional weapons, traditional dances, traditional clothes, traditional houses, folk songs) which developed is very suitable for use in the learning process of Social Sciences (IPS).